2021
DOI: 10.1002/jimd.12389
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics revealed changes in phospholipids during the development of neuroinflammation in Abcd1tm1Kds mice and X‐linked adrenoleukodystrophy patients

Abstract: X‐linked adrenoleukodystrophy (X‐ALD) is the most common leukodystrophy. Despite intensive research in recent years, it remains unclear, what drives the different clinical disease courses. Due to this missing pathophysiological link, therapy for the childhood cerebral disease course of X‐ALD (CCALD) remains symptomatic; the allogenic hematopoietic stem cell transplantation or hematopoietic stem‐cell gene therapy is an option for early disease stages. The inclusion of dried blood spot (DBS) C26:0‐lysophosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In search for disease biomarkers, VLCFAs incorporated at the sn-1 position of phosphatidylcholine and phosphatidylethanolamine were found to be enriched in Abcd1 null mice, similar to a profile seen in fibroblasts from Zellweger spectrum disorder patients (Hama et al, 2018). More recently, the induction of experimental autoimmune encephalitis (EAE, achieved by injecting a truncated MOG peptide with bacterial adjuvant) in such mice resulted in decrease of both serum C20:3-LPC and C20:4-LPC in subjects in which EAE resulted in paralysis compared with null mice unaffected by the EAE or control (Kettwig et al, 2021). Translating to humans, a twofold decrease in both species was observed only in ccALD patients prior to MRI changes but not in those with positive Loes score at the time of analysis, complicating the interpretation of these findings as X-ALD-related neuroinflammation biomarkers.…”
Section: Mouse (Mus Musculus)mentioning
confidence: 53%
“…In search for disease biomarkers, VLCFAs incorporated at the sn-1 position of phosphatidylcholine and phosphatidylethanolamine were found to be enriched in Abcd1 null mice, similar to a profile seen in fibroblasts from Zellweger spectrum disorder patients (Hama et al, 2018). More recently, the induction of experimental autoimmune encephalitis (EAE, achieved by injecting a truncated MOG peptide with bacterial adjuvant) in such mice resulted in decrease of both serum C20:3-LPC and C20:4-LPC in subjects in which EAE resulted in paralysis compared with null mice unaffected by the EAE or control (Kettwig et al, 2021). Translating to humans, a twofold decrease in both species was observed only in ccALD patients prior to MRI changes but not in those with positive Loes score at the time of analysis, complicating the interpretation of these findings as X-ALD-related neuroinflammation biomarkers.…”
Section: Mouse (Mus Musculus)mentioning
confidence: 53%
“…Previous studies also indicated the effects of flavonoids on the metabolism of lipids in mice [ 54 ]. These studies showed that flavonoids and their metabolites can attach themselves to the lipid bilayer or interact with membrane receptors, which in turn modify the bilayer lipid profile [ 54 56 ]. The interaction and penetration of polyphenols with lipid bilayers depend on the structures and concentrations of the polyphenols, the compositions of the lipids, and other factors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also indicated the effects of flavonoids on the metabolism of lipids in mice (52). These studies showed that flavonoids and their metabolites can attach themselves to the lipid bilayer or interact with membrane receptors, which in turn modify the bilayer lipid profile (52-54). The interaction and penetration of polyphenols with lipid bilayers depend on the structures and concentrations of the polyphenols, the compositions of the lipids, and other factors (55).…”
Section: Discussionmentioning
confidence: 99%